2015
DOI: 10.17135/jdhs.2015.15.4.437
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbonated Water on Bovine Enamel Erosion and Plaque Adhesion

Abstract: Due to the attractive benefits with regard to bone health, digestion, and hydration, carbonated water consumption have rapidly grown over the past few years. However, the acidic drink has latent potential for enamel erosion. The most experimental studies about the enamel erosion have focused on the carbonated beverages with sugar and artificial sweeteners. Here, we determined the enamel erosion potential by commercially available carbonated waters with bovine teeth. The erosion was verified by pH value, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In a previous study, 21 calcium ions were released into the carbonated water after bovine teeth were immersed in carbonated water. The concentration of calcium ions from the bovine teeth increased over time and continued, and moreover detection of the calcium ion was performed after several hours of immersion in carbonated water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, 21 calcium ions were released into the carbonated water after bovine teeth were immersed in carbonated water. The concentration of calcium ions from the bovine teeth increased over time and continued, and moreover detection of the calcium ion was performed after several hours of immersion in carbonated water.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of calcium ions from the bovine teeth increased over time and continued, and moreover detection of the calcium ion was performed after several hours of immersion in carbonated water. In this study, the immersion time was shorter than that in the previous study, 21 and the test solutions were remade and refreshed at the beginning of every experimental session to minimize the effect of the calcium ions released from the teeth. In addition, calcium ions were added as calcium chloride, based on a previous study, 20 because sodium chloride has been reported to have a negligible influence on the potential of erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Residual tissue and plaque were removed from the permanent incisor, and specimens measuring 5×5 mm were prepared using a cutting disc 7) . The specimens were randomly divided into four groups (n=10 in each group).…”
Section: Analysis Of Dental Plaque Formationmentioning
confidence: 99%
“…Its cause can be divided as intrinsic and extrinsic factor. The former includes nervous or spontaneous vomit, and gastrointestinal disorder; the latter, dietary factors e.g., soda like coke and vitamin C in acid foods, fruits 6) , and energy drink containing low pH or citric acid 7,8) , carbonated water 9) . Another can be occupational dental erosion caused by job environment, the place to be dealt with acid 4) .…”
Section: Introductionmentioning
confidence: 99%